Raw bovine milk as a reservoir of yeast with virulence factors and decreased susceptibility to antifungal agents - Moravkova, Monika; Huvarova, Veronika; Vlkova, Hana; Kostovova, Iveta; Bacova, Romana (Medical mycology, 2021)
In recent years, increased rates of yeast infections in humans and animals have been recognized worldwide. Since animals may represent a source of yeast infections for humans, knowing the antifungal susceptibility profile of yeast isolates from milk and evaluating their pathogenic potential would be of great medical importance. Therefore, the aim of this survey was to study yeast diversity in milk samples, analyze the hemolytic and phospholipase activities of isolates and determine minimal inhibition concentration (MIC) for fluconazole, voriconazole and flucytosine. Out of 66 yeast isolates obtained from 910 individual raw milk samples from subclinically infected cows, 26 different yeast species were determined based on sequencing of the D1/D2 and ITS regions. Among them, Pichia kudriavzevii (formerly known as Candida krusei), Kluyveromyces marxianus (formerly known as Candida kefyr) and Debaryomyces hansenii (formerly known as Candida famata) were the most commonly identified. Hemolysin and/or phospholipase activity was observed in 66.7% of isolates. The elevated MIC for fluconazole was determined in 16 isolates from 11 species. The findings of this study demonstrate that yeast isolates from raw milk have the potential to express virulence attributes such as hemolysin and phospholipase, and additionally, some of these strains showed elevated MIC to fluconazole or to flucytosine.LAY SUMMARY: We identified 66 yeast isolates, including 26 different yeast species from 910 individual milk samples. Our results indicate that individual milk samples may serve as a source of yeasts with the potential to trigger infection and may have reduced sensitivity to tested antifungal agents.
Keywords: Cattle; Animals; skot; Virulence Factors; flukonazol; Antifungal Agents; Microbial Sensitivity Tests; Female; Fluconazole; zvířata; mléko; mikrobiální testy citlivosti; Voriconazole; antifungální látky; vorikonazol; faktory virulence; ženské pohlaví; Milk